Characterization of Durum Wheat Genotypes by Seed Storage- Protein Electrophoresis - Tofiq, Sherwan I.; A.Muhammed, Aram; Ameen, Taban N. Hamma (Sulaimani Journal for Pure and Applied Sciences, 2012)
Durum wheat grains from twenty five genotypes of 5x5 diallel crosses, which includes 20 crosses and 5 parents, were collected. Analyzing of seed storage –proteins for all genotypes done by sodium dodcyle sulphate polyacrylamide gel electrophoresis(SDS- PAGE). Evaluation of Genetic composition for HMW and LMW of glutenin and gliadin unit bands were done by comparing the results and number of bands and pair bands with the reference standards, results showed high rate of quality in addition to adaptation to local environment, results supported by measuring protein % and Ash% and color pigments.
Keywords: Durum wheat genotypes; SDSPAGE; HMW; LMW; Color pigments